RNA Polymerase RPOTp is Involved in C‐to‐U RNA Editing at Multiple Sites in Arabidopsis Chloroplasts - Nadia Ahmed Ali; Wenjian Song; Yayi Zhang; Jiani Xing; Kexing Su; Xingxing Sun; Yujia Sun; Yizhou Jiang; Dianxing Wu; Xiaobo Zhao (Advanced Science)
Abstract RPOTp is the nuclear‐encoded plastid‐targeted RNA polymerase and plays a crucial role in chloroplast gene expression. Transcripts in plant organelles are altered by the conversion of cytidine (C) to uridine (U) at specific positions through RNA editing. However, whether RPOTp is involved in chloroplast RNA editing remains unclear. Here, the role of RPOTp in C‐to‐U RNA editing at multiple sites in Arabidopsis chloroplasts is uncovered. Multiple organellar RNA editing factor 2 (MORF2) is required for the editing of most sites in chloroplasts. RPOTp is identified from the co‐immunoprecipitation targets of MORF2. The sca3‐2 mutant, defective in RPOTp, exhibits a pale‐yellow phenotype and alters the RNA editing of nine sites in chloroplasts. It is also shown that RNA editing is uncoupled from chloroplast transcriptional activity. RPOTp directly interacts with chloroplast multiple‐site RNA editing factors, including MORF2, MORF8, MORF9, and ORRM1. It is further shown that RPOTp participates in RNA editing by influencing the dimerization of MORF proteins. The defect in RPOTp impairs the expression of most chloroplast genes, indicating an indispensable role for RPOTp in chloroplast gene expression. These findings reveal that RPOTp not only participates in transcription but also has a novel role in RNA editing of chloroplast transcripts.